Taking CSR to heart relationship between CSR and Filipino consumers' purchase behavior - Amparo, J. S. (2003)
Corporate social responsibility (CSR) refers to the activities, programs and projects implemented by the companies that aim to contribute to development. With the growing popularity of CS among corporations in the country, there is a need to validate whether SR affects the purchase behavior of Filipino consumers. This study aimed to look at how a company's CS affects consumers' purchase behavior. Based on the study, the majority of the consumers were more brand conscious than company conscious. Although, majority of them were not aware of CS and did not factor in CS in their current consumer purchase decision, there was high potential that they would consider it in their future purchased decisions. This was evident in their answer, wherein 80% were willing to patronize a product if they knew of its CSR programs. Consumers were even willing to switch brands and to pay more if they knew that the product's or service's company have CSR programs. Companies could greatly benefit from their CSR if they would let people know more about their CSR initiatives. They should position themselves as a socially responsible company that provides first and foremost quality and right priced products.
Keywords: Consumer behavior